An Empowerment of Electronic Applications-Community-Based Nutrition Recording and Reporting (E-Ppgbm) in the Work Area of Nias Selatan District - Asniwati Lase; Sri Lestari Ramadhani Nasution; Ermi Girsang (Sean Institute, 2024)
The nutritional status of toddlers in the August 2021 e-PPGBM showed that the prevalence of stunted toddlers in South Nias Regency was 22%. This figure is lower when compared to the prevalence of stunting in 2020. This research aims to analyze the use of the Electronic Community-Based Nutrition Recording and Reporting Application (E-PPGBM) in the South Nias Regency Work Area. Quantitative research design with a cross sectional study design approach. A sample of 36 people was obtained by total sampling. Quantitative data was analyzed univariate, bivariate and multivariate, qualitative data was analyzed using interactive analysis. Based on the results of quantitative research at the univariate stage, it is known that of the 43 respondents, the majority were aged 36-45 years, namely 29 (80.6%), were female, namely 22 (61.1%), had a bachelor's degree, namely 26 (72), 2%) respondents. Bivariate results show that there is an influence of system quality (p=0.000), information quality (p=0.000), service quality (p=0.005) on user satisfaction of the e-PPGBM application in the South Nias Regency Work Area. The most dominant variable is the information quality variable with a p value of 0.005, OR = 57.502 (95% CI = 3.448-959.078). The suggestion in this research is that the health service can increase user satisfaction by improving the quality of the e-ppgbm application by providing access to information on health and nutrition services.